Social Norms and Entrepreneurial Intent of Graduating University Students in North West Nigeria - Kabir Abbas, Muhammad; Osunsan, Olutayo K.; Kibuuka, Muhammad (European Journal of Business and Management Research, 2020)
This study investigated the correlation between social norms and entrepreneurial intent of graduating university students in North West Nigeria. The study adopted quantitative research design. The study population was graduating students from seven universities selected from among the fourteen universities in Northwest Nigeria. A sample size of 379 was estimated from 24,000 graduating students using Krejcie and Morgan (1970) table. However, 364 questionnaires were retrieved. Simple random sampling was used to select the students who participated in the study. Data analysis was conducted using correlation analysis, and linear regression analysis of the study variables. The study revealed a positive and significant relationship between social norms and entrepreneurial intent (r=.721**p=0.000<0.001). Furthermore, the study revealed that social norms can significantly explain 51.8% of the variation in entrepreneurial intent (Adjusted R2=0.518, p=0.000<0.05). The study concluded that appropriate social norms enhance development of entrepreneurial intent in students. The study recommended that the management of universities such as directorates of student welfare should put in place environments that promote building appropriate social norms among students.
Keywords: Social Norms; Entrepreneurial Intent; Entrepreneurship; Northwest Nigeria